2011
DOI: 10.1111/j.1745-7599.2011.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of appropriate use criteria for stress myocardial perfusion imaging at two academic medical centers: Compliance and association with image findings

Abstract: Most studies at both sites were classified as appropriate. At UWMC, the likelihood of a study classified as appropriate demonstrating an abnormality was not significantly different from a study classified as uncertain or inappropriate. AUC are imperfect tools but are increasingly created and referenced; as such, it is vital that practicing nurse practitioners are knowledgeable about their creation, application, and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…1020,3444 The results of our search strategy are illustrated in Figure 1. The 2005 AUC were used by 6 studies, 16,18,19,39,42,44 and the remainder used the 2009 AUC. 1015,17,20,3438,40,41,43 Single-photon emission computed tomography (SPECT) was the modality utilized in most of the studies, 1320,3436,38,39,4144 one study reported using positron emission tomography (PET), 12 while the remainder of the studies did not specify.…”
Section: Resultsmentioning
confidence: 99%
“…1020,3444 The results of our search strategy are illustrated in Figure 1. The 2005 AUC were used by 6 studies, 16,18,19,39,42,44 and the remainder used the 2009 AUC. 1015,17,20,3438,40,41,43 Single-photon emission computed tomography (SPECT) was the modality utilized in most of the studies, 1320,3436,38,39,4144 one study reported using positron emission tomography (PET), 12 while the remainder of the studies did not specify.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 122 citations, 34 met inclusion criteria and were selected for full-text review and data extraction. These articles included 6 articles and 6 cohorts for the stress echocardiography 2008 AUC,[ 11 , 13 17 ] 6 articles and 8 cohorts for the stress echocardiography 2011 AUC,[ 13 , 17 21 ] 10 articles and 11 cohorts for the stress MPI 2005 AUC,[ 22 31 ] and 18 articles and 21 cohorts for the stress MPI 2009 AUC. [ 14 , 20 , 23 , 30 , 32 45 ] Some studies contributed multiple cohorts to our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] Similarly, for stress MPI 2005 AUC, Soine et al contributed two cohorts (one cohort underwent testing at University of Washington Medical Center and the second cohort underwent testing at the Veterans Health Administration of Puget Sound). [ 31 ] Each cohort is separately presented in the figures (note that enrollment dates are rounded to the nearest year).…”
Section: Resultsmentioning
confidence: 99%